Recycling of Municipal Solid Waste (MSW) as a resource for bioproducts development - Marsi, Noraini; Main, Nor Mazlana; Leman, Abdul Mutalib; Mahmood, Salwa; Mat Hassan, Nik Normunira (Penerbit UTHM, 2021)
Over the years, the world population have increase multiple times. It affected the number of product waste since the production of making product is increase. This will drive us to higher environmental impact. To overcome the problem, there are different numbers of product end-of-life (EOL) option that can be used based on the product characteristics. The right selected option can reduce the environmental impact. There are suitable method that can be used to determine the EOL of product option and all the methods do not consider using the material, ecological, economic and social parameters to decide the choice of product EOL. Therefore, this project aimed to develop a methodology for determination of product end-of-life option. The development of methodology is considering all the criteria needed to get the better result of paper product EOL option.